(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Circuit training may have significant development on physical fitness of human beings. So the researcher purposes to study the Effect of Circuit Training on Abdominal Muscular Strength and Leg Explosive Power among Volleyball players. For this purpose, 30 men players from different Colleges Affiliated to Veer Narmad South Gujarat University, Surat. For this purpose, 30 men players age group of 18 to 25 years were selected at random. They were distributed into two groups, group I was treated as, experimental group and group II was treated as control group. Experimental group was given six weeks Circuit Training and the control group was not given any treatment. Physical Fitness variables on Muscular Strength and leg explosive power it was assessed through Sit-ups, Vertical jump test. The data were collected before and after the training period and collected data was computed by dependent’s’ T test in all cases level of significance was fixed at 0.05 level. The result concluded that there was significant development on Muscular Strength and leg explosive power level due to the influence of Circuit Training than the control group among volleyball player.